The effect of turmeric (Curcuma longa) supplementation on the performance and economic efficiency of local crossbred chickens - Linh, Nguyen T. (Asia-Pacific Journal of Science and Technology, 2023)
The experiment involving a total of 120 local crossbred chickens within the age range of 5 to 13 weeks old was systematically sorted into four treatments groups with three replicates per treatment group. This study aims to quantify the effect of turmeric powder supplementation in diets on the growth performance and economic efficiency of these chickens. A completely randomized design was used for this study wherein the birds had ad libitum access to feed and water in all the treatment groups. Different inclusion levels of turmeric were used in the diets, as follows: 0, 0.250, 0.500, and 0.750%. The result of the study showed that dry matter (DM), crude protein (CP), ether extract (EE), nitrogen-free extract (NFE), crude fiber (CF), ash, and metabolizable energy (ME) were lower in the 0.75% turmeric treatment group than in the other group. In addition, turmeric increased the daily weight gain (DWG), final live weight and improved the feed conversion ratio (FCR) in the group supplemented with 0.750% turmeric (p<0.05). However, feed intake was lowest in the 0.750% turmeric treatment (p<0.05). Furthermore, the 0.75% turmeric treatment was more profitable than the other treatments. It can be concluded that the inclusion of 0.75% turmeric in the experiment had strong effects on chicken performance and economic efficiency.